Promoting innovation at school: a tool to improve learning programming and assessment - Szpunar, Giordana; Consoli, Gianluca; Sposetti, Patrizia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2020)
This article proposes a tool aimed at improving the efficacy of teaching and learning processes at school. Developed on the basis of the action research paradigm, the format enhances strong interactions among learning programming, selection of learning strategies, and evaluation. In virtue of its flexible structure, the model can have different implementations, stemming from the programming concerning single disciplines to the construction of the school curriculum. However, in all its potential uses, the format facilitates the realization of teaching and learning processes inspired to the key competencies’ framework.